2017
DOI: 10.1177/0033294117715479
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Well-Being in Israel and Palestine: The Subjective Well-Being Assessment Scale

Abstract: This work presents the psychometric properties of the Subjective Well-Being Assessment Scale in a sample of 423 participants composed of Israeli Arabs and Palestinians from the West Bank/Gaza Strip. Psychometric assessment of the instrument was based on confirmatory factor analysis. The convergent and discriminant validity of Subjective Well-Being Assessment Scale were also tested via administration of the General Health Questionnaire and the Positive and Negative Affect Scale. The results suggest that Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…Subjective Wellbeing Assessment Scale (SWBAS; Veronese et al, 2017): The SWBAS is a quantitative instrument originally developed to measure SWB in the Arab context. All questionnaire items were translated and back translated from the original standard English version of the questionnaire following the procedure described in the dedicated section above.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective Wellbeing Assessment Scale (SWBAS; Veronese et al, 2017): The SWBAS is a quantitative instrument originally developed to measure SWB in the Arab context. All questionnaire items were translated and back translated from the original standard English version of the questionnaire following the procedure described in the dedicated section above.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Next, multiple-group CFA (MGCFA; Byrne, 1998; Veronese et al, 2017) was performed to test measurement invariance across two parallel sets of data, with a view to enhancing the ecological validity of the results. Specifically, the invariance of both parts (A and B) of the SWBAS measurement model was evaluated across gender-based cohorts of adolescents.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Regarding specific dimensions of culture, research points to the protective impact of spiritual or religious beliefs (i.e., Pargament et al, 2011) as well as strong affiliation with ethnic identity (i.e., Han et al, 2016). For example, recent research by Veronese et al, 2017 pointed to the protective impact of spirituality and sense of meaning amongst trauma exposed Palestinian aid workers in the Gaza Strip. In fact, the researchers demonstrated that participants with the highest levels of trauma exposure could experience resilience through spiritual and religious affiliations.…”
Section: Introductionmentioning
confidence: 99%
“…In general, quantitative studies have demonstrated severe impairments in Palestinians’ subjective well-being and quality of life (Mataria et al, 2009; Harsha et al, 2016). Perceptions of social instability, humiliation, and psychological suffering have been associated with lower levels of well-being (Giacaman et al, 2007a; Veronese et al, 2017). Qualitative research that concentrated on Palestinians’ quality of life revealed a holistic and fluctuating characterization of mental and physical well-being, including reports of a lack of happiness, diminishing energy and competency, a sense of fragmentation, physical complaints, and illness (Giacaman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Checkpoints vary in material, form, placement, and function and impose different requirements for passage (Giacaman et al, 2011; Harsha et al, 2016). However, movement is only possible using a pass system, which identifies every Palestinian by mechanisms such as a color code or a biometric identification card that can be applied for (Veronese et al, 2017). …”
Section: Introductionmentioning
confidence: 99%